Constraints to attendance at visitor attractions: the case of museums, zoos and botanic gardens - Nowacki, Marek (Turyzm/Tourism, 2015)
The paper has employed a three-factor model of constraints, which differentiates intrapersonal, interpersonal and structural. The study was carried out on a sample of N = 981 adult residents of Poland. The three most common barriers constraining attendance at attractions were identified: availability, high entrance fees and lack of time. The constraints were found to be related to a number of socio-demographic characteristics, such as gender, age, education, size of place of residence and household income per capita. Three market segments limited by similar constraints and showing similar attraction attendance behaviour were identified with their socio-demographic characteristics.